IMPROVING STUDENTS PRONUNCIATION USING PICTURE AT THE FIFTH YEARS OF SD N MOJOKERTO 2 KEDAWUNG SRAGEN - LANITA, DEWI (2010)
This research aims to describe four things, namely the implementation of teaching English pronunciation using picture, the improvement result of students achievement, the students responses on the implementation of teaching pronunciation by the pictures and the difficulties of the fifth year students of SD N Mojokerto 2 Kedawung Sragen in learning pronunciation using the pictures. In achieving the objectives of the research, the writer uses Classroom Action Research procedure which involves four steps, namely planning, implementing, observing, and reflecting. The research is held in SD N Mojokerto 2 Kedawung Sragen. The writer takes the fifth years that consist of twenty students as the subject of the study. The data will be analyzed by these steps: (1) reducing data, (2) explaining data and (3) drawing conclusion or verification. There are two cycles in this research in which each is conducted in three meetings. After analyzing the data, the writer describes the result of the research indicating the mean score at the pre-test is 5.9. In pos-test 1, the mean score is 7.3. In post-test 2, the mean score is 8. The results of pre-test and post-test indicate that the students have a significant improvement in pronouncing the words. The students also have a positive response, such as: they are not bored, they can be motivated and easier in learning English pronunciation; the students' looked braver and more confident, beside that, they looked enthusiastic and more active in the classroom during the lesson. The result of the students' response and the mean scores before treatment and after treatment indicates that the students' have improvement in achieving the English pronunciation. So, it can be said that the teaching pronunciation using picture is successful.